If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + -393)(x + 4) = 0 Reorder the terms: (-393 + X)(x + 4) = 0 Reorder the terms: (-393 + X)(4 + x) = 0 Multiply (-393 + X) * (4 + x) (-393(4 + x) + X(4 + x)) = 0 ((4 * -393 + x * -393) + X(4 + x)) = 0 ((-1572 + -393x) + X(4 + x)) = 0 (-1572 + -393x + (4 * X + x * X)) = 0 (-1572 + -393x + (4X + xX)) = 0 Reorder the terms: (-1572 + 4X + -393x + xX) = 0 (-1572 + 4X + -393x + xX) = 0 Solving -1572 + 4X + -393x + xX = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '1572' to each side of the equation. -1572 + 4X + -393x + 1572 + xX = 0 + 1572 Reorder the terms: -1572 + 1572 + 4X + -393x + xX = 0 + 1572 Combine like terms: -1572 + 1572 = 0 0 + 4X + -393x + xX = 0 + 1572 4X + -393x + xX = 0 + 1572 Combine like terms: 0 + 1572 = 1572 4X + -393x + xX = 1572 Add '393x' to each side of the equation. 4X + -393x + 393x + xX = 1572 + 393x Combine like terms: -393x + 393x = 0 4X + 0 + xX = 1572 + 393x 4X + xX = 1572 + 393x Reorder the terms: -1572 + 4X + -393x + xX = 1572 + 393x + -1572 + -393x Reorder the terms: -1572 + 4X + -393x + xX = 1572 + -1572 + 393x + -393x Combine like terms: 1572 + -1572 = 0 -1572 + 4X + -393x + xX = 0 + 393x + -393x -1572 + 4X + -393x + xX = 393x + -393x Combine like terms: 393x + -393x = 0 -1572 + 4X + -393x + xX = 0 The solution to this equation could not be determined.
| 2x+5(2.5)=20 | | 27=(27-15x)*2 | | 5779/19= | | -100=0.1x(30+-1x) | | -100=0.1(30-x) | | arccos(3/5) | | 4--7= | | 65+70=78 | | 12/x=6/11 | | x/2=3/10 | | 12/x=6/9 | | -55+b+39.68=-71.03 | | -55+b+39.68=71.03 | | 10z+1=3z+6 | | 5x-80x^2=0 | | 3x^3-9=0 | | 1=8tan(2x+1)-3 | | 4/25-x^2/81 | | 4(m+1)= | | 9x^2-9x+4=7x^2 | | 2x^3+6x^2+6x+6=0 | | 6a-3(a-3)=21 | | 8(b+5)-3=61 | | 4x-9=8x-17 | | 20-8n=2n | | 10x+45=8x+57 | | 9a-5(a-2)=18 | | 6a-2(a-5)=22 | | 8(b+3)-3=61 | | 9(b+6)-3=78 | | 8x-8=12x-16 | | 3+3x=11-1x |